Equity Valuation of Telepizza Group - Pinto, João Filipe dos Reis (2017)
The dissertation aims to value the pizza foodservice company Telepizza Group. The main objective is to suggest a fair value for the share in order to ultimately support a buy, hold or sell recommendation vis a vis the market value as per November 4th 2016. The dissertation first provides an introduction over the methods commonly used in equity valuation. Afterwards, the industry dynamics and new consumption trends are assessed. Additionally, the company and its business model are analysed in detail as well. The following step is valuation. A DCF approach was performed to value Telepizza which was complemented with a relative analysis. Both methods supported the same recommendation. Finally, a conclusion section summarizes what investors should take away from this dissertation. A one-page investment case is also provided where the reader may easily understand the view this dissertation supports on Telepizza share. This dissertation issues a BUY recommendation with a Fair Value of EUR4.93 per share, implying a 15% upside to the current market price of EUR4.30 per share. This recommendation is in line with BPI equity research team and the main differences between both valuations are assessed.